2010
DOI: 10.1107/s010876731004287x
|View full text |Cite
|
Sign up to set email alerts
|

Practical applications of averages and differences of Friedel opposites

Abstract: The practical use of the average and difference intensities of Friedel opposites at different stages of structure analysis has been investigated. It is shown how these values may be properly and practically used at the stage of space-group determination. At the stage of least-squares refinement, it is shown that increasing the weight of the difference intensities does not improve their fit to the model. The correct form of the coefficients for a difference electron-density calculation is given. In the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 24 publications
5
65
0
Order By: Relevance
“…The validation of a structure analysis of a non-centrosymmetric crystal structure by way of plots of observed against model values of the average (A) and difference (D) intensities of Friedel opposites has been introduced by Flack et al (2011). The average and difference of Friedel opposites are defined by…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation of a structure analysis of a non-centrosymmetric crystal structure by way of plots of observed against model values of the average (A) and difference (D) intensities of Friedel opposites has been introduced by Flack et al (2011). The average and difference of Friedel opposites are defined by…”
Section: Introductionmentioning
confidence: 99%
“…A compound with an appreciable resonant-scattering contribution has D(hkl) approximately 0.01A(hkl), whereas a compound with a small resonant-scattering contribution has D(hkl) approximately 0.0001A(hkl). Flack et al (2011) made a study of 29 crystal structures published in 2007. It was found that these crystal structure determinations could be separated into three categories based on the appearance of the D obs against D model plot of the acentric reflections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very much in line with the technique of comparing bond distances and angles from one particular crystal-structure determination with those given in tables of standard values. However, Dr David Watkin of the University of Oxford had the inspiration of looking at the fit of the observed to the model (calculated) intensities (Flack et al, 2011) It would seem appropriate to make some remarks based on personal experience, concerning crystallographers' understanding of the subject area of absolute structure and absolute configuration. In general, there is a deep rift in the comprehension of the subject between:…”
mentioning
confidence: 99%
“…This is very much in line with the technique of comparing bond distances and angles from one particular crystal-structure determination with those given in tables of standard values. However, Dr David Watkin of the University of Oxford had the inspiration of looking at the fit of the observed to the model (calculated) intensities (Flack et al, 2011). It is customary to plot |F obs | 2 against |F model | …”
mentioning
confidence: 99%